HPV Associated Squamous Cell Carcinoma in the Rectal Tonsil. (May 2023) - Desai, Ketav; Baskovich, Brett; Alkhasawneh, Ahmad; Mohamed, Khaled; Omman, Reeba; Gopinath, Arun
Mucosa-associated lymphoid tissue has been reported throughout the gastrointestinal tract including rectum. Rarely, a nodular proliferation of predominantly submucosal lymphoid tissue in the rectum has been documented as rectal tonsil. Here we report a patient with HPV-associated squamous cell carcinoma of the rectal tonsil, presenting as a polyp. Previously, rare reports of HPV-associated lymphoepithelial carcinoma have been reported in the literature. We are presenting an extremely rare occurrence and emphasizing the importance of appropriate nomenclature based on the pathogenesis of the neoplasm.